2019
DOI: 10.3389/fgene.2018.00710
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of norA, Coding for a Main Efflux Pump of Staphylococcus aureus

Abstract: NorA is the best studied efflux system of Staphylococcus aureus and therefore frequently used as a model for investigating efflux-mediated resistance in this pathogen. NorA activity is associated with resistance to fluoroquinolones, several antiseptics and disinfectants and several reports have pointed out the role of efflux systems, including NorA, as a first-line response to antimicrobials in S. aureus. Genetic diversity studies of the gene norA have described three alleles; norAI, norAII and norAIII. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…no pre-mature stop codons or frameshift mutations). In line with previous work 45 , we found that the norA coding sequence is polymorphic, and we identified polymorphisms in a previously characterized norA promoter region 46 48 . However, the P values associated with these polymorphisms are 1000 times higher than the conservative significance threshold used in our GWAS analysis, suggesting that these associations are true negatives.…”
Section: Resultssupporting
confidence: 90%
“…no pre-mature stop codons or frameshift mutations). In line with previous work 45 , we found that the norA coding sequence is polymorphic, and we identified polymorphisms in a previously characterized norA promoter region 46 48 . However, the P values associated with these polymorphisms are 1000 times higher than the conservative significance threshold used in our GWAS analysis, suggesting that these associations are true negatives.…”
Section: Resultssupporting
confidence: 90%
“…This finding suggests a delicate balance in the tolerable expression levels of norA, which, in turn, places a theoretical limit to the degree of norA overexpression-mediated resistance that can occur in a strain. Beyond norA expression, it is worth mentioning that a recent report defined three possible norA alleles (17). It is intriguing to speculate that these various alleles may have different functional consequences in terms of norAmediated antiseptic resistance; however, this topic remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, norA was recently described as part of the core genome of S. aureus, but was shown to exist as multiple possible alleles (17). norA is known to impart resistance to a variety of structurally diverse compounds, and previous work suggests that NorA may be responsible for the majority of basal antiseptic resistance in S. aureus (37,38).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…When induced by substrates in the environment for a long time, efflux system-encoding genes are activated and expressed, and the ability to efflux drugs is greatly enhanced, thus leading to drug resistance (Zarate et al, 2019). Active drug efflux systems play a role in resistance to multiple drugs (Costa et al, 2018). There are three types of multidrugpumping proteins present on the Staphylococcus aureus cell membrane: QacA, NorA, and Smr (Foster, 2016;Jang, 2016).…”
Section: Efflux Systemsmentioning
confidence: 99%